Strategy For Managing The Potential Of The Fisheries Sector In The Economic Growth Of The Indonesia-Malaysia Border Coastal Region - Reo Zaputra; Muslimin H Kara; Rahman Ambo Masse; Sumar’in (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to analyze the potential of the fisheries sector in Sambas Regency using the Location Quotient (LQ) and Shift-Share approaches, as well as to formulate management strategies to encourage economic growth in the Indonesia-Malaysia border region. With a qualitative approach, this research integrates normative-theological, sociological, and scientific analyses, using data from the 2015-2019 period collected through interviews, observations, and documentation, and analyzed using LQ, Shift-Share, and SWOT. The research results show that the fisheries sector is a leading sector with an average LQ value of 2.75, reflecting its ability to meet local and export needs, while the Shift-Share analysis reveals the competitive advantage of this sector in regional economic growth. This research produces strategic recommendations including the improvement of facilities and infrastructure, technology adoption, human resource development, and institutional strengthening. This result is expected to serve as a reference for local governments in formulating policies to optimize the fisheries sector as a driving force for the border economy. This study recommends improving fisheries facilities and infrastructure, adopting modern technology, and strengthening institutions and regulations to improve the competitiveness of the fisheries sector in Sambas Regency. In addition, human resource development through training and diversification of fisheries businesses needs to be done to improve the welfare of fishermen. Optimizing the trade and export of fishery products is also the main strategy in encouraging economic growth in the Indonesia-Malaysia border region.